What is the value of fibre-endoscopic evaluation of swallowing (FEES) in neurological patients? A cross-sectional hospital-based registry study. Issue 3 (6th March 2018) - Braun, Tobias; Juenemann, Martin; Viard, Maxime; Meyer, Marco; Fuest, Sven; Reuter, Iris; Kaps, Manfred; Prosiegel, Mario; Tanislav, Christian
Abstract : Objectives: Fibre-endoscopic evaluation of swallowing (FEES) to detect dysphagia is gaining more and more importance as a diagnostic tool. Therefore, we have investigated the impact of FEES in neurological patients in a clinical setting. Design: Cross-sectional hospital-based registry. Setting: Primary acute care in a neurological department of a German university hospital. Participants: 241patients with various neurological diseases who underwent FEES procedure. Primary and secondary outcome measures: Dysphagia and related comorbidities. Results: 267 FEES were performed in 241 patients with various neurological diagnoses. Dysphagia was diagnosed in 68.9% of the patients. In only 33.1% of the patients, appropriate oral diet was chosen prior to FEES. A relevant dysphagia occurred more often in patients with structural brain lesions (83.1% vs 65.3%, P=0.001), patients with dysphagia had a longer hospitalisation (median 18 (IQR 12–30) vs 15 days (IQR 9.75–22.75), P=0.005) and had a higher mortality (8.4% vs 1.3%, P=0.041). When the oral diet was changed, we observed a lower pneumonia rate (36% vs 50%, P=0.051) and a lower mortality (3.7% vs 11.3%, P=0.043) in comparison to no change of oral diet. A restriction of oral diet was identified more often in older patients (median 75 years (IQR 66.3–82 years) vs median 72 years (IQR 60–79 years), P=0.01) and in patients with structural brain lesions (86.8% vs 73.1%, P=0.05). Conclusion: On clinical investigation, dysphagia was misjudged for the majority of the patients. FEES might help to compensate this drawback, revising the diet regime in nearly 70% of the patients.